The devil is in the detail. Disclosing the impact of religion on the milk system in Ethiopia - D’Haene, Eline (Afrika Focus, 2020)
The influence of religion within food systems in developing economies has been understated in scholarly studies. With its different Christian, Islamic, and traditional faiths, Ethiopia offers a promising field for investigating the impact of religion on the milk system, the most important animal protein source in Ethiopian diets. In a first chapter, we investigate how the presence of a religious fasting period influences household milk intake in the country. The second and third chapter explore how milk producers have adapted to the demand seasonality caused by religious fasting practices in two different major milk production areas. In the two final chapters we investigate if and how religious ties facilitate milk transactions. This dissertation concludes that religious fasting practices have a clear impact on milk consumption and production in the country, thereby creating considerable market inefficiencies. Furthermore, we find evidence of market coordination problems along. KEY WORDS: COORDINATION PROBLEMS, DEMAND SEASONALITY, ETHIOPIA, MILK SYSTEM, RELIGION